Benefits of triple-layer remote phosphor structure in improving color quality and luminous flux of white LED - Thuc Minh Bui; Phan Xuan Le; Dinh Hoang Bach; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2019)
Remote phosphor structure has higher luminous efficiency comparing to that of both conformal phosphor and in-cup phosphor structures. However, it is hard to control the color quality of remote phosphor structure, and this issue has become one of the most researchable objectives to many researchers in recent years. Up to now, there are two remote phosphor structures applied to improve the color quality, including dual-layer phosphor configuration and triple-layer phosphor configuration. The purpose of this research is to select one of those configurations to have multi-chip white LEDs (WLEDs) achieved the highest color rendering index (CRI), color quality scale (CQS), luminous efficacy (LE), and color uniformity. In this research, WLEDs with two correlated color temperatures (CCT) of 6600K and 7700K were applied. The obtained results showed that triple-layer phosphor configuration is more outstanding in CRI, CQS, and LE. Moreover, the color deviation has been significantly reduced, which means the color uniformity has been enhanced with the application of triple-layer phosphor configuration. These results can be proven by scattering properties of phosphor layers based on Mie theory. Thus, the researched results have become a reliable and valuable reference for manufacturing higher-quality WLEDs.